Transition protocol from subcutaneous treprostinil to intravenous epoprostenol in deteriorating patients with pulmonary arterial hypertension. (1st May 2020) - Mouratoglou, Sophia Anastasia; Patsiala, Anthoula; Feloukidis, Christos; Karvounis, Haralambos; Giannakoulas, George
Abstract: Background: Despite advantages in the treatment options of pulmonary arterial hypertension, continuous parenteral prostanoid administration, although often complicated by serious side effects, remains the treatment of choice for patients with advanced disease. The need of transitioning from one parenteral prostanoid agent to the other is often faced in the daily clinical practise. Up to today, there is no established transition protocol from subcutaneous treprostinil to intravenous epoprostenol. Methods: A staggered approach to subcutaneous treprostinil down-titration with simultaneous epoprostenol up-titration is described. Subcutaneous treprostinil is down-titrated by 5 ng/kg/min every 5 h while intravenous epoprostenol is up-titrated by 2 ng/kg/min every 2 h. Results: The designed protocol was implemented in 4 patients with pulmonary arterial hypertension (3 women, median age 70.5 (range 38–79) years). Median starting subcutaneous treprostinil dose was 44.5 (range 37–100) ng/kg/min and median treprostinil down-titration time was 32.5 (range 25–85) hours. The median maximal epoprostenol dose was 36 (range 28–90) ng/kg/min, achieved in 36 (range 30–90) hours. Only mild prostanoid-related side effects were reported. Conclusions: The proposed staggered transition protocol from subcutaneous treprostinil to intravenous epoprostenol was safe in a limited number of patients with pulmonary arterial hypertension. Highlights: A transition protocol from subcutaneous treprostinil to intravenous epoprostenol was designed. Subcutaneous treprostinil was down-titrated in a staggered approach of 5 ng/kg/min every 5 h. Intravenous epoprostenol was up-titrated in a staggered approach of 2 ng/kg/min every 2 h. Transition was guided by prostanoid-related side effects. Transition was successful in a small patient population.